Microgametophyte Development in Cannabis sativa L. and First Androgenesis Induction Through Microspore Embryogenesis - Galán-Ávila, Alberto; García-Fortea, Edgar; Prohens, Jaime; Herraiz, Francisco Javier (Frontiers in Plant Science, 2021)
Development of double haploids is an elusive current breeding objective in Cannabis sativa L. We have studied the whole process of anther and pollen grain formation during meiosis, microsporogenesis, and microgametogenesis and correlated the different microgametophyte developmental stages with bud length in plants from varieties USO31 and Finola. We also studied microspore and pollen amyloplast content and studied the effect of a cold pretreatment to excised buds prior to microspore in vitro culture. Up to 476,903 microspores and pollen grains per male flower, with in vivo microspore viability rates from 53.71 to 70.88% were found. A high uniformity in the developmental stage of microspores and pollen grains contained in anthers was observed, and this allowed the identification of bud length intervals containing mostly vacuolate microspores and young bi-cellular pollen grains. The starch presence in C. sativa microspores and pollen grains follows a similar pattern to that observed in species recalcitrant to androgenesis. Although at a low frequency, cold-shock pretreatment applied on buds can deviate the naturally occurring gametophytic pathway toward an embryogenic development. This represents the first report concerning androgenesis induction in C. sativa, which lays the foundations for double haploid research in this species.